A high-temperature hybrid absorption-compression heat pump for waste heat recovery. (15th September 2018) - Liu, Changchun; Jiang, Yingchun; Han, Wei; Kang, Qilan
Highlights: An absorption-compression heat pump for 0.5 MPa saturated steam is studied. Exergy loss distribution of the hybrid system was declared. The sensitivity variations of the exergy efficiency has been revealed. Provide the foundation for the saturated steam production by waste heat. Abstract: An absorption-compression heat pump is a promising way to recover low-temperature waste heat efficiently in industrial applications. In this paper, an advanced ammonia-water absorption-compression heat pump is proposed to recover the sensible heat of flue gas below 150 °C to generate saturated steam at 0.5 MPa (151.8 °C). The sensible heat is cascade utilized in the hybrid heat pump system. The high-temperature waste heat is recovered to generate pure ammonia vapor in the rectifier, and the low-temperature heat is used to evaporate the ammonia liquid. In the ammonia vapor compression process, the gas compression process is combined with a liquid compression process, leading to the clear decrease in power consumption. The simulation results indicate that the coefficient of performance and exergy efficiency of the proposed system reaches 5.49 and 27.62%, which is almost two times and 4.69% higher than that of the reference system, respectively. Subsequently, a sensitivity analysis is conducted to optimizing the key parameters, and the optimums values are obtained. Finally, an economic analysis is adopted to evaluate the economic performance of the proposed system. The payback period of the proposed system is 6.26 years compared to the reference system. This study may provide a new way to produce saturated steam by efficiently using the low-temperature waste heat.